Influences of alpine ecosystem degradation on soil temperature in the freezing-thawing process on Qinghai-Tibet Plateau - Hu, H. C.; Wang, G. X.; Liu, G. S.; Li, T. B.; Ren, D. X.; Wang, Y. B.; Cheng, H. Y.; Wang, J. F.; 刘广山 (2009)
The alpine ecosystem is very sensitive to environmental change due to global and local disturbances. The alpine ecosystem degradation, characterized by reducing vegetation coverage or biomass, has been occurring in the Qinghai-Tibet Plateau, which alters local energy balance, and water and biochemical cycles. However, detailed characterization of the ecosystem degradation effect is lack in literature. In this study, the impact of alpine ecosystem degradation on soil temperature for seasonal frozen soil and permafrost are examined. The vegetation coverage is used to indicate the degree of ecosystems degradation. Daily soil temperature is monitored at different depths for different vegetation coverage, for both permafrost and seasonal frozen soils. Results show that under the insulating effort of the vegetation, the freezing and thawing process become quicker and steeper, and the start of the freezing and thawing process moves up due to the insulating effort of the vegetation. The influence of vegetation coverage on the freezing process is more evident than the thawing process; with the decrease of vegetation coverage, the integral of frozen depth increases for seasonal frozen soil, but is vice versa for permafrost.